Challenges of reducing urban social inequality in an Amazonian city - Bastos , Ananda Brito; Ferreira, José Francisco de Carvalho; Freitas, Josimar da Silva (Electronic Journal "Fórum Ambiental da Alta Paulista", 2024)
This study assesses the evolution of social exclusion in the urban area of Macapá, Amapá, between 1991 and 2010. This is an associational research approach with interference between variables, based on statistical data and quantitative and comparative methods. The study highlights the debate on intraurban social conditions within the context of medium-sized cities in the Amazon. The results indicate that social exclusion in Macapá is more strongly correlated with indicators of quality of life than income autonomy, and that process of social integration occurred slowly. Here, we conclude that despite some significant advancements, the social inclusion process in Macapá has been low, particularly in terms of basic sanitation indicators.